Rabindranath Tagore: the ruined nest and other stories - Quayum, Mohammad Abdul (translator) (Silverfish Books, 2014)
A collection of short stories by Asia's first Nobel Laureate, Rabindranath Tagore (1861-1941), edited and translated by Mohammad A. Quayum. The book contains 20 translated shorts stories, as well as a biographical essay on the author and an introduction.